Performance analysis of incremental cooperative relaying system over composite multipath/shadowing fading channels - HENGWei-jun CHENG; Yan HUANG (Tongxin xuebao)
Since the performance metrics of digital communication systems over composite multipath/lognormal fading channels is intractable,a mixture Gamma (MG) fading model is used to approximate Nakagami-lognormal (NL) fading model.By using MG fading channel model,some exact closed-form expressions of the average error rate and outage probability for incremental cooperative relaying system are obtained,respectively,where per hop is independent and non-identically distributed.Finally,numerical and simulation results are shown to verify the accuracy of the analytical results.These results show that it is helpful to approximate the composite NL distribution by using the MG distribution in the performance analysis of cooperative relaying systems.